Patterns of Urban Housing Shape Dengue Distribution in Singapore at Neighborhood and Country Scales - Osama M. E. Seidahmed; Deng Lu; Chee Seng Chong; Lee Ching Ng; Elfatih A. B. Eltahir (GeoHealth, 2018)
Abstract Dengue is the most important human arboviral disease in Singapore. We classified residential areas into low‐rise and high‐rise housing and investigated the influence of urban drainage on the distribution of dengue incidence and outdoor breeding at neighborhood and country scales. In Geylang area (August 2014 to August 2015), dengue incidence was higher in a subarea of low‐rise housing compared to high‐rise one, averaging 26.7 (standard error, SE = 4.83) versus 2.43 (SE = 0.67) per 1,000 people. Outdoor breeding drains of Aedes aegypti have clustered in the low‐rise housing subarea. The pupal density per population was higher in the low‐rise blocks versus high‐rise ones, 246 (SE = 69.08) and 35.4 (SE = 25.49) per 1,000 people, respectively. The density of urban drainage network in the low‐rise blocks is double that in the high‐rise ones, averaging 0.05 (SE = 0.0032) versus 0.025 (SE = 0.00245) per meter. Further, a holistic analysis at a country‐scale has confirmed the role of urban hydrology in shaping dengue distribution in Singapore. Dengue incidence (2013–2015) is proportional to the fractions of the area (or population) of low‐rise housing. The drainage density in low‐rise housing is 4 times that corresponding estimate in high‐rise areas, 2.59 and 0.68 per meter, respectively. Public housing in agglomerations of high‐rise buildings could have a positive impact on dengue if this urban planning comes at the expense of low‐rise housing. City planners in endemic regions should consider the density of drainage networks for both the prevention of flooding and the breeding of mosquitoes.